Response of Mycorrhiza-Inoculated Pepper and Amino Acids to Salt Treatment at Different Ratios. Issue 3 (4th February 2019) - Basak, Hakan; Çimrin, K. Mesut; Turan, Metin; Güneş, Adem; Ozlu, Ekrem
ABSTRACT: Mycorrhiza has attracted interest as one of the microorganisms that increase a crop's salt stress tolerance. This study was conducted to determine the impacts of mycorrhiza inoculation and applying salt at different ratios on the yield of peppers and amino acid concentrations. The study was conducted in greenhouse conditions on loamy soils with four salt treatments, two mycorrhiza inoculations and a control in a complete randomized block design. The present study indicated that salt treatment alone was significantly correlated with crop stem and root amino acid concentrations, RWC% and leaf sizes, whereas applying mycorrhiza showed a positive relationship to stem height, stem and root wet weight, and root amino acids but led to a decloine in root serine and glutamine, and stem amino acid and glutamine. In conclusion, inoculating with mycorrhiza was observed to make a positive contribution to salt stress tolerance at different levels in almost all the parameters examined.